Genome-wide Association Study Reveals New Loci Associated With Pyrethroid Resistance in Aedes aegypti - Cosme, Luciano V.; Lima, José Bento Pereira; Powell, Jeffrey R.; Martins, Ademir Jesus (Frontiers in Genetics, 2022)
Genome-wide association studies (GWAS) use genetic polymorphism across the genomes of individuals with distinct characteristics to identify genotype-phenotype associations. In mosquitoes, complex traits such as vector competence and insecticide resistance could benefit from GWAS. We used the Aedes aegypti 50k SNP chip to genotype populations with different levels of pyrethroid resistance from Northern Brazil. Pyrethroids are widely used worldwide to control mosquitoes and agricultural pests, and their intensive use led to the selection of resistance phenotypes in many insects including mosquitoes. For Ae. aegypti, resistance phenotypes are mainly associated with several mutations in the voltage-gated sodium channel, known as knockdown resistance (kdr). We phenotyped those populations with the WHO insecticide bioassay using deltamethrin impregnated papers, genotyped the kdr alleles using qPCR, and determined allele frequencies across the genome using the SNP chip. We identified single-nucleotide polymorphisms (SNPs) directly associated with resistance and one epistatic SNP pair. We also observed that the novel SNPs correlated with the known kdr genotypes, although on different chromosomes or not in close physical proximity to the voltage gated sodium channel gene. In addition, pairwise comparison of resistance and susceptible mosquitoes from each population revealed differentiated genomic regions not associated with pyrethroid resistance. These new bi-allelic markers can be used to genotype other populations along with kdr alleles to understand their worldwide distribution. The functional roles of the genes near the newly discovered SNPs require new studies to determine if they act synergistically with kdr alleles or reduce the fitness cost of maintaining resistant alleles.